2018
DOI: 10.1038/s41598-018-32687-6
|View full text |Cite
|
Sign up to set email alerts
|

Simple separation of good quality bovine oocytes using a microfluidic device

Abstract: We fabricated a simple microfluidic device for separation of bovine oocytes based on the oocyte quality to improve the conception rate of in vitro fertilization (IVF) by using good quality oocytes. The microfluidic device separates oocytes based on sedimentation rate differences in a sucrose buffer, which is dependent on oocyte quality. The microfluidic device has a 700 µm width, 1 mm height, and 10 mm long separation channel. Oocytes were injected from the upper half of the separation channel, and they flowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
(38 reference statements)
0
16
1
Order By: Relevance
“…One technology that has seen implementation in the field of assisted reproduction is microfluidics, for both IVP of embryos and cryopreservation ( Zhao and Fu, 2017 ; Weng, 2019 ). In cattle, microfluidic devices have been developed for sorting more viable sperm ( Li et al, 2016 ) and oocytes ( Iwasaki et al, 2018 ). A microfluidic apparatus containing bovine oviductal epithelial cells that is illustrated in Figure 7 has been used to support fertilization and embryonic development through day 4 of development ( Ferraz et al, 2018 ).…”
Section: Some Ways Forwardmentioning
confidence: 99%
“…One technology that has seen implementation in the field of assisted reproduction is microfluidics, for both IVP of embryos and cryopreservation ( Zhao and Fu, 2017 ; Weng, 2019 ). In cattle, microfluidic devices have been developed for sorting more viable sperm ( Li et al, 2016 ) and oocytes ( Iwasaki et al, 2018 ). A microfluidic apparatus containing bovine oviductal epithelial cells that is illustrated in Figure 7 has been used to support fertilization and embryonic development through day 4 of development ( Ferraz et al, 2018 ).…”
Section: Some Ways Forwardmentioning
confidence: 99%
“…By using a similar technique, a simple separation of submillimeter-sized particles reach 90, 90, 85, 65 and 55% degree of separation for 20, 30, 60, 90 and 150 L min -1 flow rate, respectively [18]. On the other hand, a simple separation of bovine oocytes has been performed within seconds, which is remarkable for biochemistry field [19].…”
Section: Separation Engineeringmentioning
confidence: 99%
“…Thus, morphological assessment only considers the indirect features of oocyte quality, such as cytoplasmic homogeneity, and the amount and quality of somatic cells in the cumulus-oocyte complex (BAKRI et al, 2016). Although this approach is widely used, it is quite subjective and its accuracy is limited, because some oocytes with normal morphology might be in an early stage of degeneration, leading to heterogeneous results (IWASAKI et al, 2018). Besides morphological evaluation of the oocytes, follicular characteristics have been used as well to improve IVP (DE BEM et al, 2014;IWASAKI et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although this approach is widely used, it is quite subjective and its accuracy is limited, because some oocytes with normal morphology might be in an early stage of degeneration, leading to heterogeneous results (IWASAKI et al, 2018). Besides morphological evaluation of the oocytes, follicular characteristics have been used as well to improve IVP (DE BEM et al, 2014;IWASAKI et al, 2018). A previous study assessed the competence of bovine oocytes from varying follicles sizes and demonstrated that large follicles increased oocyte quality and blastocyst production, as compared to medium and small follicles (LABRECQUE et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation